Murcha de Fusário do Caupi: Caracterização do patógeno e potencial de Trichoderma spp. no manejo - Cruz, José Manoel Ferreira de Lima (2021)
Cowpea beans (Vigna unguiculata L.) is a socioeconomically important crop that shows great losses in productivity due to several factors, such as the occurrence of diseases. Among the diseases that affect this crop, the fungus of the genus Fusarium stands out, that are widely distributed in the soil and cause seed rot and Fusarium wilt. In the search for alternatives to reduce the use of synthetic fungicides on seeds, the use of fungi of the genus Trichoderma, which predominate in the rhizosphere of different plant species, have potential in the control of phytopathogens, in addition to helping to promote plant growth. The aims of this work were to carry out the morphological and pathogenic characterization of Fusarium spp., to select Trichoderma isolates with potential for phosphate solubilization, indole-3-acetic acid synthesis and growth promotion, as well as to evaluate the antagonism between Fusarium sp. x Trichoderma spp. The study was conducted at the Phytopathology Laboratory (LAFIT) belonging to the Federal University of Paraiba. Two hundred and fifty strains of Trichoderma and Fusarium were obtained and fifty isolates of each genus were selected based on the morphological characteristics to perform the proposed tests. The Fusarium spp. strains were isolated from infected cowpea seeds, 'Semper verde', 'Corujinha', 'BRS Marataoã', 'BR 17 Gurguéia' and 'Costela-de-Vaca', obtained from rural producers in the Brejo Paraibano region and those from Trichoderma spp. were isolated from soil samples of the Mata do Pau Ferro State Park, Areia -PB. The most virulence isolate of the pathogen was confronted with ten isolates of the antagonist with potential for biocontrol, in vitro and in vivo with plants of cowpea cv. 'Sempre verde'. It was observed that Fusarium sp. showed a wide morphological variability, mainly in relation to colony pigmentation, mycelial growth rate index and micromorphological characteristics. Regarding pathogenic characterization, 80% of isolates were pathogenic to cowpea crop. The isolates of Trichoderma spp. presented morphological differences in relation to pigmentation, mycelial growth rate index and conidia production, in addition to different levels in the phosphates solubilization and indole-3-acetic acid synthesis, where they presented initial growth promotion with the ability to colonize the roots of cowpea. The isolates of Trichoderma spp. tested in the control of Fusarium spp. showed production of volatile, non-volatile metabolites, mycoparasitism activity and inhibition in the germination of conidia, being efficient in reducing the incidence and disease severity, in addition to promoting an increase in photosynthetic processes and in the integrity of the plant's plasma membrane. Probably the cowpea Fusarium wilt is caused by more than one species of Fusarium and the genus Trichoderma from the Atlantic Forest biome has potential in the management of this disease.